Activation of hippocampal nuclear factor-κB by retrieval is required for memory reconsolidation - Boccia, M. (2007)
Initially, memory is labile and requires consolidation to become stable. However, several studies support that consolidated memories can undergo a new period of lability after retrieval. The mechanistic differences of this process, termed reconsolidation, with the consolidation process are under debate, including the participation of hippocampus. Up to this point, few reports describe molecular changes and, in particular, transcription factor (TF) involvement in memory restabilization. Increasing evidence supports the participation of the TF nuclear factor-κB (NF-κB) in memory consolidation. Here, we demonstrate that the inhibition of NF-κB after memory reactivation impairs retention of a hippocampal-dependent inhibitory avoidance task in mice. We used two independent disruptive strategies to reach this conclusion. First, we administered intracerebroventricular or intrahippocampal sulfasalazine, an inhibitor of IKK (IκB kinase), the kinase that activates NF-κB. Second, we infused intracerebroventricular or intrahippocampal κB decoy, a direct inhibitor of NF-κB consisting of a double-stranded DNA oligonucleotide that contains the κB consensus sequence. When injected immediately after memory retrieval, sulfasalazine or κB decoy (Decoy) impaired long-term retention. In contrast, a one base mutated κB decoy (mDecoy) had no effect. Furthermore, we also found NF-κB activation in the hippocampus, with a peak 15 min after memory retrieval. This activation was earlier than that found during consolidation. Together, these results indicate that NF-κB is an important transcriptional regulator in memory consolidation and reconsolidation in hippocampus, although the temporal kinetics of activation differs between the two processes. Copyright © 2007 Society for Neuroscience.